THE DIFFERENCES IN MEANING BETWEEN MUSLIM WOMEN'S MODEST CLOTHING AND WOMEN'S CLOTHING ADVERTORIALS - Adara, Reza Anggriyashati; Fadliyah, Annisa; Primasari, Winda (Leksema: Jurnal Bahasa dan Sastra, 2024)
Modest fashion has progressed positively in the last two decades. Designers and advertisers are trying to attract modest fashion’s consumers. One of the mediums to promote it is by advertorials. Analyzing words and phrases used in advertorials can help advertisers, practitioners and other concerned parties to understand how advertorials are written. Using Leech’s theory toward meanings, this study aimed to analyze and compare the differences between the advertorials of Muslim women modest clothing and women's clothing from semantic perspective. This study applied a descriptive qualitative approach by analyzing four advertorials of women’s modest, formal, and casual clothing. The results of this study show that the advertorials of modest clothing seem to use a thematic meaning by creating the images of comforted and elegant looking Muslim women in modest clothes. On the other hand, the advertorials of women’s formal and casual clothing look to portray the wearers as sexy and confident women. Although both types of advertorials give meanings with empowering themes, they explore different aspects of empowerment to give understanding toward their potential consumers.